Is the positive c-kit immunostaining associated with the presence of cells analogous to the intersticial cells of Cajal in the ciliary muscle? - Paula,Jayter Silva (2009)
PURPOSE: Interstitial cells of Cajal were identified in the gastrointestinal tract of several species, with close relation to the enteric nervous system. Since it was recognized that interstitial cells of Cajal express the gene product of c-kit, we performed immunohistochemistry for c-kit protein in ciliary muscle specimens of monkeys' eyes. METHODS: Eight eyes from four adult male new world monkeys (Cebus apella) were studied. After blocking endogenous peroxidase activity and nonspecific protein binding, 1:100 dilution of mouse monoclonal antibody against c-kit human oncoprotein was applied to tissues. Antigen-antibody reaction was visualized using the avidin-biotinylated horseradish peroxidase complex in each slide. RESULTS: We observed some groups of fusiform c-kit expressing cells located amongst muscle bundles of the ciliary muscle. Other pigment cells and mast cells were also observed. CONCLUSION: C-kit expressing cells observed in the ciliary muscle of Cebus apella, showed no similarity to melanocytes or mast cells and they could be associated with their gastrointestinal interstitial cells of Cajal counterpart.